2013
DOI: 10.2147/mder.s55197
|View full text |Cite
|
Sign up to set email alerts
|

Safety and 6-month effectiveness of minimally invasive sacroiliac joint fusion: a prospective study

Abstract: BackgroundSacroiliac (SI) joint pain is an often overlooked cause of low back pain. SI joint arthrodesis has been reported to relieve pain and improve quality of life in patients suffering from degeneration or disruption of the SI joint who have failed non-surgical care. We report herein early results of a multicenter prospective single-arm cohort of patients with SI joint degeneration or disruption who underwent minimally invasive fusion using the iFuse Implant System®.MethodsThe safety cohort includes 94 sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 38 publications
(48 reference statements)
2
33
0
Order By: Relevance
“…The type and number of postsurgical adverse events in our study was commensurate with other published studies using this device system 15,2426. The most commonly reported complications in the cohort reported herein were trochanteric bursitis and piriformis syndrome.…”
Section: Discussionsupporting
confidence: 87%
“…The type and number of postsurgical adverse events in our study was commensurate with other published studies using this device system 15,2426. The most commonly reported complications in the cohort reported herein were trochanteric bursitis and piriformis syndrome.…”
Section: Discussionsupporting
confidence: 87%
“…A total of 18 articles were identified. The study design and number of these are as follows: 10 retrospective single-center case series, 12,34,35,37,38,[44][45][46][47][48] 2 prospective single center case series, 36,49 1 multi-center retrospective case series, 50 1 single center, 27 and 2 multicenter 26,28 comparative cohort studies, one prospective single-arm study, 24 and one prospective multicenter randomized controlled trial 39 (Table 1). Two types of implants are represented: 3 studies reported the use of a single hollow modular anchorage (HMA) screw packed with demineralized bone matrix and 15 described the placement of a series (typically 3) of triangular, porous titanium plasma spray (TPS) coated implants.…”
Section: Resultsmentioning
confidence: 99%
“…non-weight bearing status), open surgical repair is typically reserved for only the most severe cases. 24,25 More recently, minimally invasive surgical (MIS) methods have become available. Compared to open surgery, minimally invasive techniques are typically associated with less blood loss, shorter hospital stay, and less perioperative morbidity; these are likely attributable to smaller surgical incisions and less soft tissue dissection.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, 15 of 18 patients were discharged on the same day as their procedure using the SImmetry system, resulting in a shorter mean length of stay than other MIS systems [45]. These data are in contrast with other MIS procedures or open fusion, which routinely require a hospital stay of 1 to 5 days [31, 45, 46]. …”
Section: Discussionmentioning
confidence: 99%